Scaling Ethereum 2.0s Cross-Shard Transactions with Refined Data Structures - Alexander Kudzin; Kentaroh Toyoda; Satoshi Takayama; Atsushi Ishigame (Cryptography, 2022)
(1) Background: To solve the blockchain scaling issue, sharding has been proposed; however, this approach has its own scaling issue: the cross-shard communication method. To resolve the cross-shard communication scaling issue, rollups have been proposed and are being investigated. However, they also have their own scaling limitations, in particular, the degree of compression they can apply to transactions (TXs) affecting how many TXs can be included in one block. (2) Methods: In this paper, we propose a series of novel data structures for the compiling of cross-shard TXs sent using rollups for both public and private Ethereum. Our proposal removes redundant fields, consolidates repeated fields, and compresses any remaining fields in the rollup, modifying its data structure to compress the address, gas, and value fields. (3) Results: We have shown that our proposals can accommodate more cross-shard TXs in a block by reducing the TX size by up to 65% and 97.6% compared to the state-of-the-art in public and private Ethereum, respectively. This compression in TX size results in an over 2× increase in transactions per block (TPB) for our proposals targeting both types of Ethereum. (4) Conclusions: Our proposals will mitigate the scaling issue in a sharded blockchain that utilizes rollups for cross-shard communication. In particular, it will enable such sharded Ethereum networks to be deployed for large-scale decentralized systems.